Teacher Competence Based on the Gospel of Matthew - Ana Lestari Uriptiningsih; Muner Daliman (Jurnal Pendidikan Agama Kristen (JUPAK), 2022)
Christian education is part of many types of ministry that are essential in all Christ-centered learning activities. But there are still some Christian Education teachers who consider teaching in this field only done because of the work obligation factor. Matthew 28:20 puts pressure on the word "teach." That means that the church must be someone ready to educate every believer. The purpose of the study was to find out the Teaching Competence of Teachers Based on the Gospel of Matthew. The results found state that Jesus Christ has a Teacher Competency that must be exemplified by all teachers, especially Teachers of Christian Education so that all learners become persons who have character and are ready to serve.